12.3-W output power and 271-nm wavelength tunability of diode-double-end-pumped Tm:CALYO laser. (August 2022) - Chen, Peng; Liu, Jian; Xu, Jie; Xu, Bin; Wang, Xiaodan; Xu, Xiaodong; Xu, Jun
Highlights: We report the highest output power (12.36 W) of diode-pumped Tm:CALYO laser at 1938 nm with a slope efficiency of 53.9%. We report the broadest tunability (271 nm) for Tm:CALYO lasers. Passively Q-switched operation was also achieved with a maximum average output power of 3.81 W and pulse width of 25.9 ns. Abstract: We report on the recent progress on high-power and broadband wavelength tunability of diode-pumped Tm:CaYAlO4 (Tm:CALYO) lasers. Using a double-end pumping geometry, we have achieved a maximum output power of 12.36 W at 1938 nm, which is believed to be the highest power that have ever achieved for Tm:CALYO lasers. Moreover, we have operated 1861 nm, 1982 nm and 2032 nm lasers with maximum output powers of 8.73 W, 5.36 W and 0.73 W, respectively, by using differently coated end-face cavity mirrors. Furthermore, using a MgF2 birefringent filter, we have tuned the lasing wavelengths from 1807 nm to 2078 nm. The 271 nm wavelength range is also believed to be the broadest tunability for Tm:CALYO lasers. Passively Q-switched Tm:CALYO laser has also been demonstrated with a maximum average output power of 3.81 W. The shortest pulse width reached 25.9 ns at a repetition rate of 10.1 kHz, which led to a pulse energy of 377.22 μJ and a peak power of 14.56 kW. These results indicate clearly that the Tm:CALYO crystal is excellent as a high-power and broadband laser gain medium operating at the important 2 μm wavelength region.